Feasibility of arthroscopic autologous chondrocyte implantation in the hip using an injectable hydrogel - Thier, Steffen; Baumann, Florian; Weiß, Christel; Fickert, Stefan (HIP international, 2018)
INTRODUCTION: In the long term the treatment of articular cartilage defects of the hip has the most direct impact on the postoperative outcome and should diminish degenerative changes caused by different pathologies. The purpose of this prospective feasibility study is to describe technical aspects of arthroscopic, injectable autologous chondrocyte implantation in the hip and to report the short-term outcome. METHODS: Full-thickness cartilage defects of 13 patients were treated arthroscopically with an injectable autologous chondrocyte transplantation product (Novocart Inject, Tetec) in a 2-step surgical procedure. Patient-related outcome was assessed with iHOT 33, EQ-5D and Non Arthritic Hip Score at baseline (day before transplantation), after 6 weeks and 3, 6 and 12 months. RESULTS: 13 out of 13 patients (all men) with a mean age of 32.7 ± 6.9 years and an average defect size of 1.9 ± 1.0 cm2 were available for follow-up after a mean of 12 months (range 6-24 months). All defects were located on the acetabulum and 11 were associated with a labral lesion of 2.9 hours size. Femoroacetabular impingement (10 cam, 2 combined, 1 pincer) was the cause of all defects. An overall statistically significant improvement was observed for all assessment scores. CONCLUSIONS: In this study we present the feasibility and short-term data of an arthroscopic injectable autologous chondrocyte transplant as a treatment option for full-thickness cartilage defects of the hip. All patient-administered assessment scores demonstrated an increase in activity level, improvement in quality of life and reduction of pain after a 12-month follow-up. Further randomised controlled trails with long-term follow-up and additional morphological assessment are needed.